Uma proposta de modelo de organização para o ensino de matemática - Gilson Maekawa Kanashiro (2017)
This work contains a model that we calls multireferential, among other reasons, by adoption of several references that compose it. The adoption of this model is justified by the fact that the solutions of problems that affect Mathematics Education, particularly in Brazil, are not only the mere combination of political, economic, social or pedagogical solutions. At least, this approach is still showing a limited solution to the general problem, that of complex nature, which is related to the subject of Education. In this context, the model is the result of exploratory research, which seeks to facilitate the implementation of already identified elements or influencers of good practices, integrating them gradually into the lives of those who make use of it. In fact, one of the objectives of the model was to turn proposals in real actions and implement them in a educational routine, where teachers and students are part of an active process. Some results, derived from classroom practices, are presented and commented on, showing how the participation of teachers and students can be monitored and controlled by themselves, in a more collaborative rather than evaluative dynamic